2012
DOI: 10.1051/0004-6361/201218865
|View full text |Cite
|
Sign up to set email alerts
|

UV-driven chemistry in simulations of the interstellar medium

Abstract: Context.Observations have long demonstrated the molecular diversity of the diffuse interstellar medium (ISM). Only now, with the advent of high-performance computing, does it become possible for numerical simulations of astrophysical fluids to include a treatment of chemistry, to faithfully reproduce the abundances of the many observed species, and especially that of CO, which is used as a proxy for molecular hydrogen. When applying photon-dominated region (PDR) codes to describe the UV-driven chemistry of uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 50 publications
5
55
1
Order By: Relevance
“…Indeed, the mean column density through the cube is about 10 21 cm −2 (corresponding to A V 0.6), which is comparable to the values in the simulation of Pelkonen et al (2009), but over a much larger volume (18 pc box compared to less than 1 pc); the bulk of the gas is therefore more fragmented and radiation penetrates more easily (Levrier et al 2012). That is why we take a uniform parameter p 0 .…”
Section: Simulated Planck Observationsmentioning
confidence: 70%
“…Indeed, the mean column density through the cube is about 10 21 cm −2 (corresponding to A V 0.6), which is comparable to the values in the simulation of Pelkonen et al (2009), but over a much larger volume (18 pc box compared to less than 1 pc); the bulk of the gas is therefore more fragmented and radiation penetrates more easily (Levrier et al 2012). That is why we take a uniform parameter p 0 .…”
Section: Simulated Planck Observationsmentioning
confidence: 70%
“…Previous observations show that CH traces H 2 well in the diffuse ISM. Steady-state models by Levrier et al (2012) reproduce the observed trend of CH versus H 2 , without the need to invoke dissipation of turbulence. This might be understood from the fact that the observations sample CH in regions with a significant fraction of hydrogen in H 2 , > f H 0.1 2 ( ) up to ∼1, while CH + prefers regions of the ISM with low hydrogen fractions as H 2 , f (H 2 )<0.5.…”
Section: Ch λ-Doubled Linesmentioning
confidence: 75%
“…A linear relation between CH and H 2 column densities, N(CH)=3.5×10 −8 N(H 2 ), has been derived by Sheffer et al (2008) to A V of around 5 mag. In steady-state chemical models, on the other hand CH traces H 2 at hydrogen densities greater than about 100 cm −3 (Liszt & Lucas 2002;Levrier et al 2012). Thus in warm and dense environments such as Orion BN/KL, the relationship between H 2 and CH could be more complex, because the abundances of CH may be at least partially a result of radiative association between C + and H 2 , which are more abundant in this environment than in the ISM.…”
Section: Introductionmentioning
confidence: 99%
“…Optical and FUV measurements towards bright stars have shown that the relationship between CH and H 2 is linear and exhibits a significant scatter of 0.2 dex (Sheffer et al 2008), larger than the measurement uncertainties, and which probably reflects small variations in the physical conditions along the probed sight-lines. As shown by Levrier et al (2012), averaging over long pathlengths tends to reduce the scatter, but local variations of the CH abundance relative to H 2 cannot be excluded. The same can be true for HF as well.…”
Section: Gas Phase Carbon Abundance and C + In The Ism Phasesmentioning
confidence: 98%